The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/tid.13083
|View full text |Cite
|
Sign up to set email alerts
|

Native kidney BK virus nephropathy, a systematic review

Abstract: Background: There is a growing base of literature describing BK nephropathy (BKVN) in patients outside of the setting of kidney transplant. Previous systematic reviews of the literature have been limited by methodology or by the scope of patients included. Study Design and Methods:Systematic Review (Prospero # CRD42018088524). Setting & Population:Patients without kidney transplant who had biopsy-proven BKVN. Selection Criteria for Studies:Full-text articles that describe native BKVN patient cases.Analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Approximately, 80% of RT recipients develop BK viruria, and 5%‐10% of these patients develop BKVN within a year post‐RT with allograft loss in about 50% 2 . However, several reports of native kidney BK nephropathy in both adult and pediatric non‐RT patients have been described in the recent literature 3 . This includes patients with HSCT, non‐renal SOT, HIV, hematological malignancies, and other immunodeficiency conditions 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 80% of RT recipients develop BK viruria, and 5%‐10% of these patients develop BKVN within a year post‐RT with allograft loss in about 50% 2 . However, several reports of native kidney BK nephropathy in both adult and pediatric non‐RT patients have been described in the recent literature 3 . This includes patients with HSCT, non‐renal SOT, HIV, hematological malignancies, and other immunodeficiency conditions 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review of the literature by Shah et al, biopsy-proven BKVN developing in the setting of solid organ transplantation accounted for approximately one third of all cases occurring in the native kidney. 5 With respect to BKVN in the native kidney, review of the literature reveals 3 liver (including the case reported herein), 13 heart, 6 lung, and 1 pancreas transplant recipients. Cases are described in both pediatric and adult populations, men and women, affect differing races, with variable combinations of immunosuppression, and with antiviral management strategies.…”
Section: Discussionmentioning
confidence: 84%
“…heart, lung, liver), hematologic malignancy (variably with bone marrow transplantation), and autoimmune disease. 4,5 Biopsy-proven BKVN in liver transplant recipients has been described sparingly. Lai et al described a 59-year-old male who was 2 years status post liver transplantation and presented acutely with biopsy-proven cytomegalovirus colitis, acute kidney injury (serum creatinine of 280 µmol/L), biopsy-proven BKVN, and 754,976 copies/mL of BK-virus in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Native kidney BKV associated disease in non‐renal solid organ transplant (NRSOT) recipients has been described in case reports and series over the years, but it has not been systematically studied 12‐35 . BKV nephropathy in the NRSOT recipient has the potential to lead to chronic kidney disease (CKD) or end‐stage renal disease (ESRD) with associated morbidity and mortality 36‐38 .…”
Section: Introductionmentioning
confidence: 99%